Adult Autoimmune Enteropathy and Acquired Acrodermatitis Enteropathica: A Rare Case Report - Antigona Begolli Gerqari; Fellanza Ismajli Hoxha; Allma Kocinaj (International Journal of Biomedicine)
We present and discuss a case of adult autoimmune enteropathy (AIE) and acquired acrodermatitis enteropathica (AAE) in an 81-year-old patient with positive calprotectin levels, zinc deficiency, and anemia. AIE and AAE are distinct medical conditions characterized by gastrointestinal symptoms. These conditions rarely coexist in the same patient, and their occurrence in an elderly individual is even rarer.